The Influence of Work Motivation, Work Discipline, and Work Facilities on Employee Performance at PT. PLN (Persero) ULP Duri - Patria, agung; Machasin, Machasin; Paramitha, Anggia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to empirically prove the influence of work motivation, work discipline, and work facilities on employee performance. The research was conducted at PT. PLN (Persero) Ulp Duri and used data obtained from the distribution of questionnaires to 54 permanent employees as respondents.The sampling method in this study used saturated or census sampling, because in this study all members of the population were used as samples. This study used a statistical data analysis method using SPSS version 26. The results of this study indicate that work motivation has a positive and significant effect on employee performance, work disciplin has a positive and significant effect on employee performance, and work facilities have a positive and significant effect on employee performance. Simultaneously, work motivation, work discipline, and work facilities have a positive and significant effect on employee performance. This finding confirms the importane of management attention to motivation, discipline, and work facilities to increase employee productivity.